"Mig og min forskning" - Bilde, Per (Religionsvidenskabeligt Tidsskrift, 1989)
The article “Me and my research” (cf. Woody Allen) is an offspring of an earlier discussion between dr. Kirsten Nielsen and myself on her dissertation, There is Hope for a Tree. The Tree as Metaphor in Isaiah (Sheffield 1989, Danish edition 1985), especially on the evaluation of the function of metaphorical language. In this article I concentrate on the specific aspect of the subjective involvement in scientific research. In an attempt to push the discussion further, I here suggest a distinction between 6 different types of such subjective involvement. And whereas some of these are to be regarded positively as necessary for the research, others are to be regarded negatively as damaging for sober scientific activity. To be conscious of this situation is already a step forward in the discussion of this complicated problem. In conclusion I attempt to unfold my own subjective ideological position in its relationship to my activity as a scholar.